Pelaksanaan Manajemen Rekrutmen Tenaga Pendidik Dalam Meningkatkan Mutu Pendidikan di Madrasah Aliyah Nurul Yaqin Kabupaten Merangin - Gunawan, Hendra; Muspawi, Mohammad (JURNAL STUDI MANAJEMEN ORGANISASI, 2023)
AbstractThis study aims to learn how to carry out management recruitment of educators in improving the quality of education in Madrasah Aliyah Nurul Yaqin starting from needs analysis, analysis of selection, determination of the right candidate, selection of the most appropriate method, choice according to needs, selecting new candidates for teaching staff, to the placement of new teaching staff, the results and supporting and inhibiting factors. This study uses qualitative descriptive methods. From the results of this study, the data found can conclude that the implementation of management recruitment of educators in improving the quality of education in Madrasah Aliyah Nurul Yaqin is done in a simple and familial way. The steps taken are analysis of needs, by analyzing the conditions of the madrasah environment into the vacancy of the existing position. Job analysis, by determining the general requirements of prospective educators to fill the required vacancies, such as S1 education qualifications. Determine the right candidate, through external sources (from outside) the madrasah environment. Choose the most appropriate method, through teaching staff or school staff and advertising on social media. Calling candidates who meet the requirements tailored to the needs of madrasah and Madrasah Head policies. Selecting prospective new educators through administrative examinations or application documents as well as a complete and easy interview process by the Head of Madrasah. Placement of new teaching staff is done directly to fill the position needed at that time in accordance with the decision of the Head of Madrasah. The results of the implementation of the management of recruitment of educators by the madrasah were declared good, because every stage had been carried out. Keywords: management, recruitment of educators, quality of education